Comprehensive low-flow analysis of the Vipava river - Jelovčan, Mateja (Acta geographica Slovenica, 2022)
he article presents the results of the analysis of low flows at 5 gauging stations on the Vipava River, which has a Dinaric pluvial-nival regime (catchment area of 590 km2). The low-flow statistics show that the gauging station Vipava stands out with the lowest values. Baseflow index (BFI) values are comparable among the considered stations and are around 0.40. Relatively low BFI values indicate low soil permeability. A high similarity between the mean annual minimum 7-day flow (MAM7) and the 95th percentile exceedance discharge (Q95) at all gauging stations indicates a temperate climate. The highest flows values occur in spring and autumn, and the lowest in summer. In wet years there are relatively large fluctuations in flow, while in dry years the flow consists mainly of baseflow. This is also confirmed with the flow duration curves analysis. The seasonality analysis shows a predominant summer regime with low flows.
Keywords: analiza nizkih pretokov; lfstat package; low-flow analysis; paket lfstat; reka Vipava; Slovenia; Slovenija; Vipava River; Vipava Valley; Vipavska dolina